2017
DOI: 10.1002/jbm.b.34022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of collagen foam, poly(l‐lactic acid) nanofiber mesh, and decellularized matrices for corneal regeneration

Abstract: Corneal tissue engineering efforts to obtain corneal tissue matrices through various types of materials for the replacement of damaged tissues. In this study, three different corneal constructs were prepared and evaluated in terms of morphological, optical, and biological characteristics. Type-I collagen was used to obtain collagen foam scaffolds through dehydrothermal crosslinking, while poly(l-lactic acid) (PLLA) was used to produce both random and aligned oriented electrospun corneal constructs. Bovine corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…On the other hand, SDS‐ and HS‐treated DPCXs successfully repopulated with human keratocytes in vitro . HS has been found to be a convenient protocol for recellularization through its establishment of a more ideal environment for human keratocytes . Decellularized human corneas, by using PLA, have also been shown to have sufficient biocompatibility with human keratocytes .…”
Section: Recellularizationmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, SDS‐ and HS‐treated DPCXs successfully repopulated with human keratocytes in vitro . HS has been found to be a convenient protocol for recellularization through its establishment of a more ideal environment for human keratocytes . Decellularized human corneas, by using PLA, have also been shown to have sufficient biocompatibility with human keratocytes .…”
Section: Recellularizationmentioning
confidence: 99%
“…Sodium dodecyl sulfate is a strong ionic detergent and is the most widely used agent in corneal decellularization practices (either alone or in combination with other agents) due to its extreme efficiency in removing cells and solubilizing cellular membranes. [22][23][24][25][26][27][28][29][30] Numerous studies have reported "complete" or "sufficient" decellularization at different concentrations and exposure times. 19 with protease inhibition and continuous shaking.…”
Section: Sodium Dodecyl Sulfate (Sds)mentioning
confidence: 99%
See 1 more Smart Citation
“…Coupled with the simple preparation process and the possibility of large-scale production, the technology is very attractive to many elds, [9][10][11][12] such as the biomedical eld, lter materials, nanosensors, and nanober-reinforced composites. [13][14][15][16][17] Among them, the biomedical eld is one of the most important application elds, which includes tissue engineering, wound dressing, and drug delivery systems. [18][19][20] A number of specic articles and patents have been reported on this subject.…”
Section: Introductionmentioning
confidence: 99%
“…It was therefore approved by the Food and Drug Administration (FDA) for certain human clinical applications such as surgical sutures and some implantable devices. Recently, porous PLLA scaffolds were widely investigated in osteoblastic [32], cranial bone [22] , corneal [1], chondrocyte [2] tissue engineering, etc. However, one disadvantage of PLLA scaffold was the complications resulting from the accumulation of lactic acid produced in the process of degradation.…”
Section: Introductionmentioning
confidence: 99%